Does Motivation Improve Employees Job Performance? A Case of Absolute Hotel Services - Ali, Ahmad Amer Aafis Mohamed; Kee, Daisy Mui Hung; Singh, Abhishek; Pandey, Rudresh; Alhamlan, Hadeel; Ahmad, Khadija Mohammad; Quttainah, Majdi Anwar; Siw, Ming Yuen; Ong, Rui Suen; Narayanan, Yashwiny (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
The present study intends to examine the relationship between motivation and employees job performance in the context of hotel industry. The study chooses Absolute Hotel Services, which is one of the fastest-growing hospitality and tourism companies located on the Asian continent to specialize in hotel management, consultancy, sales and marketing among other services. The company is also affiliated to Absolute Golf Services which offers golf and event management for both public and private golf clubs. Employees morale is one of the key elements to success for a business organization. Employees morale directly affects their job quality and performance. Therefore, it is vital to motivate employees to keep them in good morale. This research also studies key factors that affect motivation.